Analysis of Agroforestry Farm Profitability and Potential Economic Value of Carbon Sequestered by Agroforest Lands in Oyo State, Nigeria - Olatoye C. Foluke; Oladimeji U. Yusuf; Sanni A. Sukurat; Abdulkadir Aishat (Journal of Agriculture and Rural Development Studies)
The potentials of agroforestry farming are yet to be fully exploited for carbon sequestration, increased crop and farmers’ income. This study estimates the agroforestry farm profitability and potential economic value of carbon sequestered by agroforest land in Oyo State, Nigeria. Three-stage sampling procedures were adopted to select 346 agroforestry farmers involved in one agroforestry practice or the other. A structured electronic questionnaire (Kobotool app) and field observation were used in collecting primary data for the 2022 cropping season. Descriptive statistics and the Net Present Value (NPV) statistics were used for the data analysis. The potential net economic value of carbon sequestered in the study area was ₦7,246.37 ($9.18) per ha. The results indicated that agroforestry practices in the study area have a huge capacity to sequester carbon and in the long run, generate additional income for smallholder farmers. Although carbon revenues drop at 0.2-0.3% of NPV, carbon payments can still generate substantial revenue for farmers especially when carbon payments are combined with other payments for environmental services provided by agroforestry. Agroforestry practice was adjudged to be profitable with the net farm income of agroforestry farmers as ₦237,966.68 ($311.12) in the last production season. Furthermore, the returns on investment were said to be at 0.63. Despite significant results recorded from agroforestry practices, there is a greater need to create better awareness among farmers on the carbon sequestration and carbon credit generating potential of agroforestry by relevant government agencies such as the Ministry of Environment.